Răspuns :
Răspuns:
a)[-2•(-3)•(-7)+(-4)]:(-4+27)=
=[-42+(-4)]:23
=-46:23
=-2
b)(-12+15+10+13):(15-28+12)=
=(3+10+13):(-13+12)
=26:(-1)
=-26
c)[23-(-14)•23]:15=
=(23+14•23):15
=345:15
=23
d)[-29-(-35)•(-29)]:(-36)=
=[-29+35•(-29)]:(-36)
=-1044:(-36)
=29
e)[104•(-13)-(-104)]:(-12)=
=(-1354+104):(-12)
=-1248:(-12)
=104
f)[(-37)-(-37)•(-37)]:(-37)=
=[-37+37•(-37)]:(-37)
=-1406:(-37)
=38.
Explicație pas cu pas:
Răspuns:
a) - 2
b) - 26
c) 23
d) 29
e) 104
f) 38
(nu știu cât e de corect deoarece m-am grăbit să le fac) ♥️